Varian Structure And Meaning Of The Word "Tokoro" In Japanese Language Sentences - Nani Sunarni; Jonjon Johana (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2018)
The word ‘tokoro’ as a noun in Japanese, is lexically equivalent to the word "place" in Indonesian, as in the phrase suzushii tokoro "cool place". This word in Japanese has a structure and meaning that varies depending on the words followed and those who follow them. The method used as the basis of the analysis is the desktiptif method. The sources of data used form of sentences which contain the word tokoro,  also analyzed based on studies of form and meaning. Based on the results of the analysis, it was identified that the word tokoro besides having a lexical meaning, also had a grammatical meaning. Grammatical meaning can be found in pseudo nouns (keishiki meishi) and as compound particles that function as conjunctions (setsuzoku joshi). Tokoro as a structure verb keishiki meishi (~ ru, ~ te iru, ~ ta tokoro) which shows time. Whereas setsuzokujoshi has a structure (1) V (~ ta) tokoro de, V ~ ru / ~ te iru dokoro dewanai, N dokorodokoroka ~ mo nai, adverbial/ particle case of tokoro ga and auxiliary particles (fuku joshi) tokoro.